2016
DOI: 10.1080/19425120.2016.1168330
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Habitat Use of Juvenile Atlantic Bluefin Tuna

Abstract: Bluefin Tuna Thunnus thynnus are highly sought after in commercial and recreational fisheries along the East Coast of North America. To appropriately assess and manage Atlantic Bluefin Tuna (ABT), it is necessary to understand their habitat use during multiple ontogenetic stages. We tagged 17 juvenile ABT in the northwest Atlantic Ocean with pop‐up satellite archival tags (PSATs) to determine environmental factors that may affect habitat use. The PSATs were deployed off the coast of Massachusetts in August and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…() suggests that new tag attachment methods and/or tag anchors, which minimize injury and potential behavioral effects, may need to be developed for the small‐bodied, laterally compressed spearfishes. In contrast, three studies with successful PSAT data reports from a combined 57 juvenile Atlantic bluefin tuna ( Thunnus thynnus ), which are small in size but have a robust body morphology, documented no tag‐associated post release mortality and only two inferred natural predation events (Galuardi & Lutcavage, ; Goldsmith, Scheld, & Graves, ; Marcek, Fabrizio, & Graves, ). Future work on the Mediterranean spearfish should assess long‐term movement patterns for a large number of individuals, identify additional spawning areas, and determine the species’ population structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() suggests that new tag attachment methods and/or tag anchors, which minimize injury and potential behavioral effects, may need to be developed for the small‐bodied, laterally compressed spearfishes. In contrast, three studies with successful PSAT data reports from a combined 57 juvenile Atlantic bluefin tuna ( Thunnus thynnus ), which are small in size but have a robust body morphology, documented no tag‐associated post release mortality and only two inferred natural predation events (Galuardi & Lutcavage, ; Goldsmith, Scheld, & Graves, ; Marcek, Fabrizio, & Graves, ). Future work on the Mediterranean spearfish should assess long‐term movement patterns for a large number of individuals, identify additional spawning areas, and determine the species’ population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Mediterranean spearfish is a target of secondary importance in the traditional Italian harpoon fishery (Romeo et al, 2015) and rare bycatch in other commercial fisheries ( morphology, documented no tag-associated post release mortality and only two inferred natural predation events (Galuardi & Lutcavage, 2012;Goldsmith, Scheld, & Graves, 2017;Marcek, Fabrizio, & Graves, 2016). Future work on the Mediterranean spearfish should assess long-term movement patterns for a large number of individuals, identify additional spawning areas, and determine the species' population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Such variability may be related to local environmental conditions, local availability of prey, or to the physiology of ABFT themselves. Marcek et al (2016), showed that juvenile ABFT in the west-Atlantic Ocean apparently spent more time below the thermocline with increasing lunar illumination during night-time, but not during daytime. It is further noteworthy to recall that surface presence of ABFT is composed of various behavioral types, including foraging behavior and horizontal migrations (Lutcavage and Kraus, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…changes in the "surface availability") of tunas can significantly affect the number of schools observed at the sea surface (Bauer et al, 2015b), accounting for this variability is a key step to provide a robust abundance index. Several studies have sought to determine the factors driving the vertical behaviour of bluefin tuna (Walli et al, 2009;Galuardi and Lutcavage, 2012;Marcek et al, 2016;Bauer et al, 2017, Eveson et al, 2018. Archival tagging data from the Atlantic Ocean have demonstrated that the vertical behaviour of ABFT is influenced by the thermal stratification of the water column (Brill et al, 2002;Walli et al, 2009;Galuardi and Lutcavage, 2012).…”
Section: Introductionmentioning
confidence: 99%